Analisis Kualitas Layanan Website XYZ Terhadap Kepuasan Pelanggan Dengan Menggunakan Metode Webqual 4.0 - Randyka Rusniantoro; Ari Kusyanti; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
E-commerce or electronic commerce, is the process of buying and selling product or services that utilize online network or internet. The quality services of a website affects the number of users accessing customer satisfaction. Xyz is one of the largest e-commerce websites for gaming community in Indonesia. In 2016, there are some issues on xyz such as ease, information given by the website, and services. Therefore, the quality of a website has a great impact to customer satisfaction. This study uses Webqual 4.0 with multiple linear regression analysis. The finding of this study show that customer statisfaction is influenced by Usability of the website and not influenced by information Quality and Service Interaction. It proves that ease of use of the website can affect customer satisfaction. This study also shows that Usabillity, Information Quality, and Service Interaction simultaneously affect customer satisfaction. It shows that the ease, information provided by the website and service on a website simultaneously can affect customer satisfaction.